Comparative Analysis of Total and Size-Fractionated Chlorophyll a in the Yellow Sea and Western Pacific - Wei, Yuqiu; Cui, Zhengguo; Wang, Xingzhou; Teng, Guangliang; Qu, Keming; Sun, Jun (Frontiers in Microbiology, 2022)
Measurements of different size-fractionated chlorophyll a concentrations (Chl a) of phytoplankton assemblages in situ are vital for advancing our understanding of the phytoplankton size structure and thus the marine biogeochemical cycle. In the present study, we thus made a comparative analysis of total and size-fractionated Chl a in the Yellow Sea (YS) and Western Pacific (WP). Our results suggested that the total Chl a was highly variable in the YS (averaging ~1.02 µg L-1), and was generally threefold to fourfold more than that in the WP (averaging ~0.30 µg L-1). The pico-sized Chl a had a significant contribution to total Chl a in the WP (range 75-88%), while the average contributions of the nano-sized and pico-sized Chl a to total Chl a in the YS were 47% and 38%, respectively, suggesting that a majority of the total Chl a in the YS was associated with nano- and picophytoplankton. Moreover, we applied the generalized additive models (GAMs) to explore the relationships between the total Chl a and that contained in each of the three size classes. These GAMs relationships suggested a continuum from picophytoplankton dominated waters to large phytoplankton (cells> 2 µm) domination with increasing Chl a. Finally, we made a comparison of the total Chl a obtained with GF/F filters and that measured from size-fractionated filtration, and revealed that their corresponding concentrations are in good agreement, indicating the size-fractionated filtration had no effect on total Chl a determination.